Impact of urinary incontinence on sexual quality of life in Portuguese adults. Issue 2 (26th April 2014) - Pereira, Henrique; Menezes, Joana
ABSTRACT Urinary incontinence (UI) is a symptom of an underlying disorder with a high prevalence, constituting an important public health problem due to its physical, psychological and social consequences. The impact it has on the individuals' quality of life is revealed in their daily activities, self‐perception, socialization, emotional health and in their sexual life. The objective of this study is to analyse the impact of incontinence on the sexual quality of life, identifying the role of the variables: gender, duration and severity of incontinence, impact of incontinence on the quality of life and type of incontinence. The sample was composed by 55 patients (54·05% male and 45·5% female) from health facilities, in Lisbon, with a mean age of 55 years, who answered a set of questionnaires, which included: the Incontinence Impact Questionnaire (IIQ‐7); the Urogenital Distress Inventory (UDI‐6); the Questionnaire on Sexual Quality of Life, male and female versions (SQoL‐F/SQoL‐M) and a sociodemographic questionnaire. The results indicate that UI has a negative impact on the sexual quality of life in general, especially if the incontinence symptoms endure for a long period of time; also the impact of UI on social relationships, and the stress UI has a significant and negative impact on the sexual quality of life. In this study, UI has a negative impact on sexual life compounded by restrictions and other negative consequences of living with urinary leakage. The authors conclude that further research is required to ascertain the full impact of UI on sexual quality of life. Finally, implications for nurses are also discussed: in addressing the sexual health of their patients, nurses have an important contribution in assuring that experiencing UI should not necessarily translate into negative sexual quality of life.